High Voltage Security System Design and Testing of Electric Car - Peng Hailan; Jiang Zhilong (Institute of Advanced Engineering and Science, 2014)
Safety design of high voltage part is the foundation of the whole automobile design; it is based on safety design requirements of the electric car, and the security function of hardware. The design the different functions of hardware modules are presented, through circuit principle diagram layout of PCB, and circuit board is made, the systems hardware test board is design according to the functional test of the system. Test results show that relative errors between the measurement of insulation resistance value of the safety system and the theoretical value is only 0.3%, thus the rationality of the design calculation model of the insulation resistance is verified. The response times of DC (direct current) contactor are higher than the national standard requirements, so the system security design meets the design requirements. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4899